Integrating natural resource resilience and agroecology: policy on protecting agricultural land from degradation in Magelang District, Central Java Province - Widayanti, Windy Kartika Putri; Marseno, Djagal Wiseso; Purwadi, Didik (Journal of Degraded and Mining Lands Management, 2024)
Although the Government of Magelang District has local policies for land protection from degradation, landslide disaster has hampered the construction of the Rehabilitation of Farm Road (RJUT) of organic rice of UPLAND program in 2022 in Bandongan Sub-District and caused loss of farmer’s agricultural land in Sawangan. This research aimed to describe the impacts of land degradation, the relevance of local policy substance to the protection of upland farmland from degradation, identify the vulnerability of natural resources and build the integration concept consisting of resilience of natural resources and agroecology. The research was conducted in Grabag, Sawangan, and Bandongan Sub-Districts. The research method was descriptive qualitative by interviewing 18 farmers and 13 key informants by purposeful sampling and field observations. Qualitative data analysis using QDA Miner software. The results showed that local policies in Regional Regulation Number 18 of 2017 concerning the Development of Competitive and Environmentally Sound Agricultural Products and the Decree of the Head of the Agriculture and Food Service Office of Magelang District Number 188.4/694/SK/20/2021 concerning Determination of Prospective Farmers and Prospective Locations (CPCL) of UPLAND Activities in Magelang District are less relevant to protect land from holistic degradation (quality and ecological due to landslides) causing vulnerability to the resilience of natural resources. Therefore, it needs innovations in the form of public policies that are comprehensive, holistic, and integral through the integration model of natural resource resilience and sustainability of irrigation systems in upland agricultural land protection systems complementing each other.